How Swiss small- and medium-sized firms assess the performance impact of mergers and acquisitions - Spyridon Arvanitis; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2012)
While previous studies on mergers and acquisitions (M&As) mostly relied on large firms, our study is based on a sample that includes all Swiss M&As that took place in the period 2006-2008, mostly of which have been SMEs. We investigate the firm characteristics that determine the innovation and economic performance of M&A. The performance measures are based on firms' assessments. These measures are regressed on a series of possible determining factors as postulated in existing theoretical and empirical literature. M&A performance is primarily affected by specific M&A characteristics, but not by general market characteristics such as demand development or competition conditions. Rather astonishingly, it is also not affected by firm characteristics such as capital intensity, human capital endowment and firm size. There is an interesting exception: innovation activities. This means that with the remarkable exception of innovation activities the level of M&A performance is determined primarily by factors of the M&A process itself.
Keywords: L20; O31; 330; mergers and acquisitions; economic performance; innovation performance; micro data; Übernahme; Innovation; Unternehmenswert; Schweiz